Psychology and cinema assisting women in the treatment of psychoactive substance dependence - Carbonera, Alexandre; Silva, Daiane Gonçalves; Nascimento-André, Maria Isabel do; Legal, Eduardo José (Revista de Psicologia da IMED, 2014)
The objective of this study was to investigate the effects of a psychological intervention, structured in the projection of cinematographic films and reflection that emerged from them, shown and discussed among women under treatment for Psychoactive Substances dependence, residents at a Therapeutical Community located in Vale do Itajaí, in the state of Santa Catarina. The method of intervention was based in a focal group, which consisted on the exhibition and discussion of cinematographic films that were guided by pre-established themes. For the evaluation of data, content analysis was used. The results indicate that this strategy had the ability to motivate participants to continue treatment, as well as it enabled the rescue of past events and reframing of these at the present. It also demonstrated that the strategy goes beyond it, and reverberates in the TC's day by day.